2011
DOI: 10.1007/s11306-011-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

LC/MS profiling of flavonoid glycoconjugates isolated from hairy roots, suspension root cell cultures and seedling roots of Medicago truncatula

Abstract: Hairy roots and suspension cell cultures are commonly used in deciphering different problems related to the biochemistry and physiology of plant secondary metabolites. Here, we address about the issue of possible differences in the profiles of flavonoid compounds and their glycoconjugates derived from various plant materials grown in a standard culture media. We compared profiles of flavonoids isolated from seedling roots, hairy roots, and suspension root cell cultures of a model legume plant, Medicago truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…However, their result was inconsistent with the results of Dong et al, who reported that the SA-induced phenolic compound accumulation was correlated to the PAL activity in S. miltiorrhiza cell cultures [19]. It was claimed that this inconsistency was apparently due to differences in plant materials used in the researches, as the secondary metabolite profiles are varied among the different plant material types of the same plant species [34].…”
Section: Discussionmentioning
confidence: 76%
“…However, their result was inconsistent with the results of Dong et al, who reported that the SA-induced phenolic compound accumulation was correlated to the PAL activity in S. miltiorrhiza cell cultures [19]. It was claimed that this inconsistency was apparently due to differences in plant materials used in the researches, as the secondary metabolite profiles are varied among the different plant material types of the same plant species [34].…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, numerous innovative MS‐based methods have been developed for profiling flavonoid glycoconjugates. A widely used approach relies on the evaluation of characteristic neutral losses occurring as a result of sequential cleavage of saccharide subunits from the intact flavonoid glycoconjugate . In addition to these so‐called top‐down profiling methods, bottom‐up and MRM‐based HPLC‐MS methods have also been recently reported for the screening of flavonoids in plants.…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent study from the Stobiecki group, difficulties with the interpretation of registered data in HPLC‐MS analyses were summarized as follows: (1) the presence of compounds with the same nominal molecular weight and different elemental compositions, which appear as isobars in low‐resolution MS and (2) the isomers of natural products with different substitutions of sugar moieties, various patterns of acylating groups on the sugar moieties, and isomerization of the aglycones (e.g. flavones and isoflavones) . The problem of isobaric compounds with different elemental formulas can be handled via the enhanced selectivity of high‐resolution mass spectrometers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS is more suitable than GC-MS for labile compounds as well as for those that are difficult to derivatize. The application of LC-MS in plant metabolomics includes the description of the tomato metabolome database (MoTo DB) [79], the identification of the accumulation of oxylipins after wound-induced stress in Arabidopsis [80], the identification of flavonoid and isoflavonoid compounds in Medicago truncatula [81], the untargeted large-scale analysis of plant metabolome [82], the characterization of metabolites that respond to stress [83, 84], and the identification of flavonoid glycoconjugates in roots form Medicago truncaluta [85]. …”
Section: Methods Used For the Determination Of Plant Metabolomesmentioning
confidence: 99%